Feminist stylistic analysis of women's intelligence in Hidden Figures by Margot Lee Shetterly - Hutabarat, Sharon Dinda N.; Lubis, Syahron; Perangin - angin, Alemina; Rangkuti, Rahmadsyah; Noor Rosa, Rusdi (Universitas Islam Sultan Agung, 2025)
This research analyzes women’s intelligence and feminism in Margot Lee Shetterly’s Hidden Figures through a feminist stylistic perspective. The objective of this study is to examine how linguistic features at the word, sentence, and discourse levels construct the representation of women’s intelligence and feminist values. This study applies a qualitative descriptive method, using Sara Mills’ Feminist Stylistic Analysis as the analytical framework. The data consist of selected words, sentences, and discourses from the novel Hidden Figures that highlight the intellectual contributions of the female characters Katherine Johnson, Dorothy Vaughan, and Mary Jackson. The analysis reveals that at the word level, elements such as generic pronouns (15 data, 6.6%) expose gender bias while also reflecting women’s resilience. At the sentence level, presupposition and inference (17 data, 7.5%) challenge societal assumptions and emphasize women’s authority. At the discourse level, focalization (16 data, 7.0%) centers women’s perspectives, validating their agency and leadership. Overall, the findings indicate that linguistic features across all levels contribute to resisting gender stereotypes and affirming women’s intellectual presence in male-dominated fields. This study enriches feminist stylistic scholarship by demonstrating how language not only reflects but also reinforces women’s agency and intellect in literature